Komposisi dan status guild komunitas ikan di Waduk Sempor Jawa Tengah - Nuning Setyaningrum; Sugiharto Sugiharto; Priyo Susatyo (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
Abstract.The functional community is described depends on the function of species in utilization food (guild). The utilization of food is a process of energy transfers in the food chain and it is represented in the pyramid of numbers. The objective of this research was to analyze the structure community of fish and the guild compositions in Sempor Reservoir. This research applied a survey with purposive random sampling technique with four station in Sempor Reservoir. Sampling at each site was taken 4 replication with interval 1 monts. The composition and status of the guild is carried out by mesuring the guild based on the position of the mouth, tooth type, gill filter type, and ratio of body length and intestine. Guilds are composed of compositions depicted by a number pyramid based on the number of species per station. The results of this reserach captured 439 individuals consists of 14 species and belong to 6 families that dominated by Cyprinidae. The number and species of fish caught were the most at the Bangkong river inlet (142 individuals) and the lowest at the center of the reservoir (60 individuals). Comparison of the composition of fish guilds at the four stations in the Sempor Reservoir shows that the number of omnivorous and carnivorous fish is obtained more than herbivorous fish. The composition of the guild at Kalianget river inlet (72.9%) and Central reservoir (42.7%) was dominated by carnivorous fish, while at Pengantalan river inlet (52.9%) and Bangkong (58.9%) were dominated by omnivorous fish. The composition of herbivorous fish is at least at all stations so that in general the composition of fish guilds in the Sempor reservoir has not been balanced.Keywords: species composition, guild, pyramid of number,Sempor reservoir Abstrak. Komunitas secara fungsional menggambarkan fungsi spesies yang ditentukan dengan pemanfaatan sumber makanan (guild). Pemanfaatan makanan dalam rantai makanan merupakan proses transfer energi dan digambarkan dengan piramida jumlah. Tujuan dari penelitian ini adalah mengkaji komposisi dan tingkat status guild komunitas ikan yang tertangkap di perairan waduk Sempor. Penelitian dilakukan dengan metode survei dan teknik purposive random sampling pada 4 stasiun di Waduk Sempor. Sampling dilakukan sebanyak 4 kali tiap bulan. Komposisi dan status guild dengan mengukur guild berdasarkan posisi mulut, tipe gigi, tipe tapis insang, dan rasio panjang tubuh dan usus. Komposisi guild digambarkan dengan piramida jumlah berdasarkan jumlah spesies per stasiun. Hasil penelitian diperoleh 439 individu terdiri dari 8 Familia dan 14 Spesies yang di dominasi familia Cyprinidae. Jumlah dan jenis individu ikan yang tertangkap paling banyak pada inlet sungai Bangkong (142 individu) dan terendah pada bagian tengah waduk (60 individu). Perbandingan komposisi guild ikan pada empat stasiun di waduk Sempor menunjukkan bahwa jumlah ikan omnivora dan karnivora lebih banyak diperoleh daripada ikan herbivora. Komposisi guild pada inlet sungai Kalianget (72,9%) dan Tengah waduk (42,7%) di dominasi oleh ikan karnivora, sedangkan pada inlet sungai Pengantalan (52,9%) dan Bangkong (58,9%) di dominasi ikan omnivora. Komposisi ikan herbivora paling sedikit pada semua stasiun sehingga secara umum komposisi guild ikan di waduk Sempor belum seimbang.Kata kunci: komposisi jenis, guild, piramida jumlah, waduk Sempor